Artificial tumor microenvironment regulated by first hemorrhage for enhanced tumor targeting and then occlusion for synergistic bioactivation of hypoxia-sensitive platesomes - Wenhui Tao; Dongyang Zhao; Guanting Li; Lingxiao Li; Songhao Li; Hao Ye; Chutong Tian; Yutong Lu; Shuying Li; Yinghua Sun; Zhonggui He; Jin Sun (Elsevier, 2022)
The unique characteristics of the tumor microenvironment (TME) could be exploited to develop antitumor nanomedicine strategies. However, in many cases, the actual therapeutic effect is far from reaching our expectations due to the notable tumor heterogeneity. Given the amplified characteristics of TME regulated by vascular disrupting agents (VDAs), nanomedicines may achieve unexpected improved efficacy. Herein, we fabricate platelet membrane-fusogenic liposomes (PML/DP&PPa), namely "platesomes", which actively load the hypoxia-activated pro-prodrug DMG-PR104A (DP) and physically encapsulate the photosensitizer pyropheophorbide a (PPa). Considering the different stages of tumor vascular collapse and shutdown induced by a VDA combretastatin-A4 phosphate (CA4P), PML/DP&PPa is injected 3 h after intraperitoneal administration of CA4P. First, CA4P-mediated tumor hemorrhage amplifies the enhanced permeation and retention (EPR) effect, and the platesome-biological targeting further promotes the tumor accumulation of PML/DP&PPa. Besides, CA4P-induced vascular occlusion inhibits oxygen supply, followed by photodynamic therapy-caused acute tumor hypoxia. This prolonged extreme hypoxia contributes to the complete activation of DP and then high inhibitory effect on tumor growth and metastasis. Thus, such a combining strategy of artificially-regulated TME and bio-inspired platesomes pronouncedly improves tumor drug delivery and boosts tumor hypoxia-selective activation, and provides a preferable solution to high-efficiency cancer therapy.